LOCAL WISDOM AS A PEDAGOGICAL FOUNDATION IN ELEMENTARY SCHOOL TEACHER EDUCATION IN NORTH MALUKU: AN EPISTEMOLOGICAL RECONSTRUCTION AND ITS IMPLICATIONS FOR TEACHER COMPETENCIES - Sitihawa Idrus (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze local wisdom as a pedagogical foundation in elementary school teacher education in North Maluku and its implications for the competencies and professional identity of prospective teachers. The research is motivated by the dominance of formal pedagogy that tends to neglect local socio-cultural contexts, resulting in learning processes that are less contextual and less relevant to the realities of students’ lives. In fact, the people of North Maluku possess a rich body of local cultural values that have the potential to serve as epistemological sources in education and learning. This study employed a qualitative approach with an ethnopedagogical design. The research was conducted in teacher education institutions (LPTK) and elementary schools in North Maluku. The research subjects included PGSD lecturers, PGSD students, elementary school teachers, and community leaders selected purposively. Data collection techniques consisted of in-depth interviews, participatory observation, and documentation studies. Data analysis used thematic analysis combined with a grounded theory approach through the stages of open coding, axial coding, and selective coding. The findings reveal that local wisdom in North Maluku embodies values of collectivity, morality, social solidarity, and contextual learning that are strongly relevant to modern pedagogical practices. The transformation of local wisdom into a pedagogical foundation occurs through processes of cultural value identification, pedagogical reinterpretation, and integration into learning design. Such integration positively contributes to strengthening pedagogical competence, reflective abilities, cultural sensitivity, and the formation of the professional identity of prospective teachers as cultural agents. However, the implementation of local wisdom-based pedagogy still faces challenges, including curriculum limitations and the limited academic capacity of lecturers to systematically integrate local cultural values. This study confirms that local wisdom can serve as an epistemological foundation for teacher education that is contextual, inclusive, and relevant to the needs of local communities.